Mantle degassing along strike-slip faults in the Southeastern Korean Peninsula - Lee, Hyunwoo (Sci Rep, 2019)
On September 12, 2016, a M(L) 5.8 earthquake hit Gyeongju in the southeastern part of the Korean Peninsula (SeKP), although the area is known to be far from the boundary of the active plate. A number of strike-slip faults are observed in heavily populated city areas (e.g., Busan, Ulsan, Pohang, and Gyeongju). However, dissolved gases related to the active faults have rarely been studied despite many groundwater wells and hot springs in the area. Here we report new results of gas compositions and isotope values of helium and carbon dioxide (CO(2)) in fault-related fluids in the region. Based on gas geochemistry, the majority of gas samples are abundant in CO(2) (up to 99.91 vol.%). Measured (3)He/(4)He ratios range from 0.07 to 5.66 Ra, showing that the mantle contribution is up to 71%. The range of carbon isotope compositions (δ(13)C) of CO(2) is from −8.25 to −24.92‰, showing mantle-derived CO(2) is observed coherently where high (3)He/(4)He ratios appear. The weakening of faults seems to be related to enhanced pressures of fluids containing mantle-derived helium and CO(2) despite the ductile lower crust underneath the region. Thus, we suggest that the SeKP strike-slip faults penetrate into the mantle through ductile shearing.